Pengaruh Investasi terhadap Pembangunan dan Pertumbuhan Ekonomi di Bandar Lampung - M. Azmi Ahnaf Tsaqif; Jenny Safira Aulia Wati; Intan Alvatyka; Ulfa Ainunisah; Yusuf Bahtiar (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2026)
Investment serves as a primary driving force in accelerating regional development and economic growth. This study aims to analyze the influence of investment on development and economic growth in Bandar Lampung City through a literature review approach based on previous research findings. As the center of trade and services in Lampung Province, Bandar Lampung holds strategic potential but continues to face challenges in infrastructure and human resource quality. The findings reveal that private investment, both Domestic Investment (PMDN) and Foreign Investment (PMA), consistently contributes positively and significantly to the growth of Gross Regional Domestic Product (GRDP) and employment absorption in Bandar Lampung. Investment generates a multiplier effect that stimulates productive sectors such as trade, services, and MSMEs. Beyond physical capital, synergy with human capital development is identified as a crucial factor in optimizing the impact of investment on community welfare. In conclusion, fostering a conducive investment climate through supportive policies and infrastructure improvement is essential to achieving sustainable economic development in Bandar Lampung.